2021
DOI: 10.3389/fimmu.2021.690069
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Involved in Metabolic Inflammation in Visceral Adipose Tissue and Liver of Transgenic Pigs

Abstract: Anti-inflammatory therapies have the potential to become an effective treatment for obesity-related diseases. However, the huge gap of immune system between human and rodent leads to limitations of drug discovery. This work aims at constructing a transgenic pig model with higher risk of metabolic diseases and outlining the immune responses at the early stage of metaflammation by transcriptomic strategy. We used CRISPR/Cas9 techniques to targeted knock-in three humanized disease risk genes, GIPRdn, hIAPP and PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…In a previous study, we performed a short-term diet-based (12 weeks) intervention on PIGinH11 pigs [16], which showed impaired glucose tolerance and varying degrees of pancreatic, hepatic, and adipose damage in PIGinH11 pigs. To investigate the pathological characteristics of the pancreas in PIGinH11 pigs and to assess its feasibility as an animal model of metabolic disorders, we evaluated the pathological histology of PIGinH11 and wild-type pigs when subjected to different durations of HFHSD and a selected 12-month dietary intervention in order to conduct snRNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we performed a short-term diet-based (12 weeks) intervention on PIGinH11 pigs [16], which showed impaired glucose tolerance and varying degrees of pancreatic, hepatic, and adipose damage in PIGinH11 pigs. To investigate the pathological characteristics of the pancreas in PIGinH11 pigs and to assess its feasibility as an animal model of metabolic disorders, we evaluated the pathological histology of PIGinH11 and wild-type pigs when subjected to different durations of HFHSD and a selected 12-month dietary intervention in order to conduct snRNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that PIGinH11 pigs exhibit impaired glucose tolerance, pancreatic fat infiltration, compensatory islet proliferation, and inflammation infiltration in the liver and visceral adipose tissue after 12 weeks of high-fat and high-sucrose diet (HFHSD) induction. They showed the typical characteristics of glucolipid metabolism disorders found in human patients [16]. In this study, we performed a prolonged HFHSD induction in transgenic and wild-type pigs.…”
Section: Introductionmentioning
confidence: 99%
“…A study in triple-transgenic model pigs suggests that CD8 T cells play a crucial role in adipose inflammation, recruiting and activating macrophages after activation in adipose tissue, which differs from our results for several reasons; we speculate, first, that CD8 T cells may not be consistently highly expressed throughout the development of the disease. Second, CD8 T cells may act more early in the development of NAFLD, and the exact cause and mechanism may need to be further explored ( Zhang et al, 2021 ). NK cells perform a fundamentally meaningful role in liver fibrosis and are generally thought to reduce fibrotic events by eliminating activated hepatic stellate cells or altering the phenotype of hepatic macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These pigs showed diabetic phenotypes such as hepatic insulin resistance and pancreatic cell apoptosis, which modeled type II diabetes better than some pigs with single‐gene modifications. Similarly, Zhang et al 35 engineered pigs to carry three knock‐in risk genes, glucose‐dependent insulinotropic polypeptide receptor ( GIPR dn ), human islet amyloid polypeptide ( hIAPP ), and Patatin‐like phospholipase domain‐containing three variant rs738409 C>G p.I148M ( PNPLA3 I148M ), resulting in glucose and lipid metabolism disorders, abnormal fat development and liver necrosis, ideal for research on non‐alcoholic fatty liver disease (NAFLD) and type II diabetes.…”
Section: Current Pig Models Of Human Diseasementioning
confidence: 99%